Otonomi Kerja dan Keamanan Psikologis dengan Mediasi Perilaku Inovatif terhadap Kinerja Pemasaran Konten di Kalangan UMKM - Sarah, Dewi; Amalia, Dinda (DFAME Digital Financial Accounting Management Economics Journal, 2026)
This study examines the influence of job autonomy and psychological safety on content marketing performance, with innovative behavior as a mediating variable among MSMEs. A quantitative approach was employed using survey data collected from 160 MSME actors in Purwakarta who are actively involved in digital marketing activities. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that job autonomy and psychological safety have significant positive effects on innovative behavior. Furthermore, innovative behavior significantly enhances content marketing performance. The mediation analysis reveals that innovative behavior plays a crucial role in linking job autonomy and psychological safety to performance outcomes. These findings suggest that internal organizational factors must be translated into innovative actions to achieve optimal marketing performance. The study contributes to the literature by providing an integrated framework that explains how employee-driven innovation influences digital marketing effectiveness in MSMEs. Practically, the results highlight the importance of fostering autonomy and creating a psychologically safe environment to encourage creativity. Despite its contributions, this study is limited to a specific regional context and cross-sectional data. Future research should explore broader contexts and additional variables to strengthen the generalizability of the findings.